Adulto mayor: familiarismo, identidad y prácticas de cuidado en familias extendidas del área semirural. Moche - 2009 - Elías Vásquez, Sheyla Noemí (2009)
The present qualitative-descriptive study was conducted in semi-rural area of Moche District, in Trujillo province. This study aimed at analyze the quotidian life of elderly people living in a extended family and so describe, identify and define conceptual basis oriented to care of elderly people living in such families. Research participants were six elderly people and their respective families, who answered the interview at home, which was recorded with the permission of interviewers. This study is based on the theoretical contributions of Tedesco and Restrepo , which presents the daily life in all its aspects and dimensions. From the speeches analysis were identified three general categories: Multidimensionality of familiarity, Culture Identity and Representations of care practices; in all of which it was demonstrated that family has become itself in the main support over the functional and psychosocial modifications that the elderly people live, getting in this way to strengthen familiar bonds and emotions that are part of a common feeling inside the family. Likewise, it showed the constant need of elderly to keeping an image of a whole and autonomous person, and also leaves a legate for the future generations and encourage the exercise of family care. The contributions of this research guide us on the need to know and understand the experiences of daily elapse of the Elderly who live in extended family, in order to IV generate nursing interventions based on theoretical approaches built and designed to promote facing the aging process and improve family dynamics. In this way, it would ensure the quality of life for the elderly and achieve greater insight into the role that nursing plays in human care.